1979
DOI: 10.1111/j.1398-9995.1979.tb04376.x
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Release of Subcutaneously Injected Antigens in the Rat: Comparison of an Aqueous Preparation with Two Alum‐Precipitated Preparations

Abstract: Release of antigen E-'*' I Tmm the site of subcutaneous injection in male rats was delayed significantly when either of two alum-precipitated preparations containing l.Ck1.2 mg ofAl/rnl was administered rather than an aqueous preparation. The rates of '*'I excretion were similarly influenced being statistically slower through the first week after single doses of the alum-precipitated preparations. The results of these studies strongly support the view that alum-precipitated vaccines offer more protection from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The particulate nature of adsorbed antigens facilitates uptake by antigen-presenting cells via phagocytosis (Mannhalter et al, 1985; Morefield et al, 2005). Adsorbed antigens are more slowly released from the injection site (Leeling et al, 1979; Weissburg et al, 1995; Noe et al, 2010), but the kinetics are highly dependent on the strength of the adsorption. Electrostatically adsorbed antigens are rapidly released and diffuse away from the injection site at a higher rate than antigens adsorbed via ligand exchange (Noe et al, 2010).…”
Section: Role Of Adsorption In the Immunostimulating Effect Of Aluminmentioning
confidence: 99%
“…The particulate nature of adsorbed antigens facilitates uptake by antigen-presenting cells via phagocytosis (Mannhalter et al, 1985; Morefield et al, 2005). Adsorbed antigens are more slowly released from the injection site (Leeling et al, 1979; Weissburg et al, 1995; Noe et al, 2010), but the kinetics are highly dependent on the strength of the adsorption. Electrostatically adsorbed antigens are rapidly released and diffuse away from the injection site at a higher rate than antigens adsorbed via ligand exchange (Noe et al, 2010).…”
Section: Role Of Adsorption In the Immunostimulating Effect Of Aluminmentioning
confidence: 99%
“…[15][16][17][18][19] The release rate of adsorbed antigen from injection site may depend on the strength of binding between antigen and aluminum. [20][21][22] Indeed, a decrease in the strength of antigen adsorption to aluminum (e.g., by phosphate pretreatment) was found to be inversely proportional to the internalization by dendritic cells in vitro 23,24 and to immunopotentiation in vivo. 15,25,26 These results are suggestive of a more efficient antigen uptake and/or processing when the antigen is poorly bound to the aluminum-containing adjuvant.…”
Section: Introductionmentioning
confidence: 99%
“…When a compound having cytotoxicity, like an aluminum-adjuvanted vaccine, persistently exists in the injured tissue, chronic immune activation can occurr and this can lead to an increased risk of autoimmune disease development (Ishihara and Hirano, 2002;Murakami and Hirano, 2012). The Al acts to keep the antigen at the site of inoculation, which may prolong the immune response at the injection site (Leeling et al, 1979;Noe et al, 2010;Hansen et al, 2009;Manhalter et al, 1985). Kashiwagi et al (2014) reported that Al containing vaccines induce inflammatory nodules at the injection site, and that the inflammatory nodules remain 6 months later.…”
Section: Discussionmentioning
confidence: 99%
“…Aluminum salt adjuvants (Als) as typified by aluminum hydroxide and aluminum phosphate have been widely used as vaccine adjuvant to elicit immunogenicity (Lindblad, 2004), such as formalin-inactivated diphtheria-pertussistetanus and conventional Salk inactivated polio vaccine (DPT-cIPV), H5N1 pandemic influenza vaccine, recombinant hepatitis B virus HBV vaccines, hepatitis A vaccine, 7-valent pneumococcal vaccine, and human papillomavirus vaccine (HPVV) in Japan. The Als have been proposed to work as adjuvant by activating innate immunity through the release of damage-associated molecular patterns (DAMPs) from injected tissues by form-ing weak cytotoxicity (Marichal et al, 2011;Kono and Rock, 2008), and Als can keep the antigen at the injection site (Leeling et al, 1979;Noe et al, 2010;Hansen et al, 2009) to promote its uptake by antigen-presenting cells, such as macrophages and dendritic cells (Morefield et al, 2005;Mannhalter et al, 1985). However, Al-containing vaccines induce some side effects as typified by local swelling, inflammation, and pain, and most of them are mild (Mark et al, 1999;Pittman et al, 2002;Gherardi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%